Unemployment, Health Outcome and Inclusive Growth in Nigeria: ARDL Bound Test Approach - Okuneye, Babatunde; Olaniyi, Oladimeji; Adekanmbi, Adewale (Acta Universitatis Danubius. Œconomica, 2023)
The main objective of this study is to examine unemployment, health outcome and inclusive growth on Nigerian economy over the period 1990-2021. Extant literature only captured a part of the whole as they either concentrate on the relationship between unemployment and inclusive growth or health outcome on inclusive growth. Consequently, the tripartite relationship among these concepts seems missing in the body of literature. This study utilized the auto-regressive distributed lag (ARDL) Bound Test technique to examine the correlation and long run relationship among variables. The empirical findings indicated a long run relationship among inclusive growth, unemployment and health outcome. Also, unemployment and health outcome have a negative and significant relationship with inclusive growth in Nigeria within the study period. Based on the findings, the paper recommended the need for the government to develop plans and policies that will expand employment opportunities and also enhance inclusive growth through increased health expenditure that will instigate the desired health outcomes.